Influence of Composition and Technological Factors on Variatropic Efficiency and Constructive Quality Coefficients of Lightweight Vibro-Centrifuged Concrete with Alkalized Mixing Water - Sergey A. Stel’makh; Evgenii M. Shcherban’; Alexey N. Beskopylny; Levon R. Mailyan; Besarion Meskhi; Denis Butko; Alla S. Smolyanichenko (Applied Sciences, 2021)
Alkalization technology and its application to obtain high-performance concrete compositions is an urgent scientific problem that opens opportunities for improving building structures. The article is devoted to the new technology of manufacturing reinforced concrete structures with low energy consumption, resource, and labor intensity based on the improved variatropic configuration of vibro-centrifuged concrete using activated water with high pH. The synergistic effect of the joint use of the proposed novel solutions has been theoretically and experimentally proved. Thus, growth in physical and mechanical characteristics of up to 15–20% was obtained, the structure and its operational ability were improved (the effectiveness of structural improvement, expressed as a percentage, reached values over 70%, concerning control samples). A positive effect on the properties of vibro-centrifuged concrete over the entire thickness of the annular section has been revealed. A method for controlling the integral characteristics of concrete has been obtained. The possibility of regulating the variatropic structure and controlling the differential characteristics of vibro-centrifuged concrete has been established. An assessment of the constructive quality and variatropic efficiency of vibro-centrifuged concrete was carried out, and new calculated dependencies were proposed, expressed in the form of relative coefficients.